Novel magnetizing technique using high temperature superconducting bulk magnets for permanent magnets in interior permanent magnet rotors. (29th June 2020) - Oka, T; Hasebe, S; Ogawa, J; Fukui, S; Nakano, T; Sakai, N; Miryala, M; Murakami, M; Yokoyama, K
Abstract: A novel magnetizing technique for permanent magnets (PMs) embedded in interior permanent magnet (IPM) motors has been proposed as a safer and more effective process than the conventional processes using copper pulse-coils. In the new process, the high temperature superconducting (HTS) bulk magnet, emitting an intense magnetic field of over 3 T, was employed to activate the rotor and PMs inside. A magnetic pole containing the HTS bulk magnet was scanned on the surface of the IPM rotor, resisting against the extremely strong attractive force between the magnet and rotor. Following experiments in the past, numerical simulation studies have been conducted to evaluate the magnetic field-trapping performances of the PMs. In this study, the numerical analysis of the magnetization behaviours was conducted for the PMs embedded in the rotor of the commercial air-conditioner motor in a hybrid car. The simulation results showed us that the demagnetized Nd-Fe-B plates in the rotor were fully magnetized in the intense static magnetic fields on the magnetic pole containing the HTS bulk magnet. The magnetizing behaviour in this peculiar magnetizing operation was made understandable by estimating the anisotropic easy-direction of the PM plates embedded in the rotor. The novel activation method for PM is characterized as a no-shock and no-heating method, which would promote the degree of freedom in the IPM motor design.